Integrating sustainable material performance and project success factors: insights from the lebanese construction sector - Mattar, Claudia; Arairo, Wahib; Khatib, Milad; Azar, Anthony (Frontiers in Built Environment, 2026)
The construction industry is undergoing a rapid transformation driven by the global urgency to minimize carbon emissions, improve material efficiency, and enhance resilience across the built environment. In developing contexts such as Lebanon, construction projects face persistent challenges related to economic instability, limited regulation, and fragmented management practices, often hindering the transition toward sustainable materials and practices. This paper presents a hybrid study combining a literature-based review of sustainability-oriented construction success factors with a Lebanese case study assessing institutional, managerial, and material-related determinants of project performance. A structured survey of 55 Lebanese construction firms was conducted to evaluate the relevance of external, institutional, and internal success factors, while integrating emerging sustainability and material performance indicators. Findings reveal that economic and technological variables, coupled with the availability of construction standards and managerial competencies, are crucial to achieving both conventional project success and sustainable material outcomes. The study highlights the pivotal role of regulatory modernization, green procurement, and material innovation; such as supplementary cementitious materials (SCMs), recycled aggregates, and smart material applications; in advancing the Lebanese construction sector toward a low-carbon future. The proposed framework connects project success factors with material performance, offering a pathway to more resilient, efficient, and environmentally responsible construction practices in developing economies.